Energy efficiency and quality of service optimization for constant bit rate real‐time applications in 802.11 networks. Issue 6 (20th February 2012) - Jimenez, Juan; Estepa, Rafael; Estepa, Antonio; Rubio, Francisco R.; Gómez‐Estern, Fabio
ABSTRACT In this paper, we propose a quality of service (QoS)‐sensitive energy efficiency optimization mechanism for 802.11 networks on the basis of the dynamic and simultaneous adjustment of the content window (W) and retry attempts limit (r) of the media access control (MAC) sublayer. The use of both operational variables let us not only find the optimum operational point regarding energy efficiency but also attain a positive impact on the QoS, which improves the results obtained with current single‐variable optimization strategies. The model under consideration includes external noise and does not impose the saturation condition in stations and as such is well suited for real‐time industrial applications under noisy channels. Results obtained from simulation confirm the advantages of adjusting simultaneously W and r versus adjusting either one separately, obtaining a slight improvement in energy efficiency and resulting in less loss and delay at the MAC sublayer. Copyright © 2012 John Wiley & Sons, Ltd.